Quarantine management procedures - Opasina, B.O.; Velez-Nauer, M. (International Livestock Centre for Africa, 1981)
Presents and discusses operation and capital cost of quarantining, purchasing policy, pattern of disease incidence. Summarises methodology for quarantine. Includes recommendations.